An Analysis of Pragmatics Study in the Film of Tarung Sarung 2020 by Archie Hekagery - Uswatunnisa (KARIWARI SMART : Journal of Education Based on Local Wisdom, 2022)
Departing from the view that meaning, language, and communication cannot be separated in everyday life, the result of this research is an analysis of the pragmatics in conversation and context depicted in the film "Tarung Sarung (2020)" which comes from the South Sulawesi area. It was found that there were 14 data for pragmatics sections, each containing 3 deixis, 2 conversations containing implicatures, 1 conversation containing presupposition, 1 face wants, 3 conversations containing politeness principles, and 4 conversations which were locutionary speech acts, perlocutions, and illocutionary (IFIDs). By using a qualitative descriptive approach and using purposive sampling, it is easier for researchers to take data which is a representative of a certain data group and present it factually and systematically.